α-Phenyl-N-tert-Butylnitrone and Analogous α-Aryl-N-alkylnitrones as Neuroprotective Antioxidant Agents for Stroke - José Marco-Contelles (MDPI AG, 2024)
The recent advances in research on the use of the antioxidant and neuroprotective agent α-phenyl-N-tert-butylnitrone (PBN) for the therapy of stroke have been reviewed. The protective effect of PBN in the transient occlusion of the middle cerebral artery (MCAO) has been demonstrated, although there have been significant differences in the neuronal salvaging effect between PBN-treated and untreated animals, each set of data having quite large inter-experimental variation. In the transient forebrain ischemia model of gerbil, PBN reduces the mortality after ischemia and the neuronal damage in the hippocampal cornu ammonis 1 (CA1) area of the hippocumpus caused by ischemia. However, PBN fails to prevent postischemic CA1 damage in the rat. As for focal cerebral ischemia, PBN significantly reduces cerebral infarction and decreases neurological deficit after ischemia using a rat model of persistent MCAO in rats. Similarly, the antioxidant and neuroprotective capacity of a number of PBN-derived nitrones prepared in the author's laboratory have also been summarized here, showing their high potential therapeutic power to treat stroke.